Analysing Intercellular Communication in Astrocytic Networks Using “Astral” - Dzyubenko, Egor; Prazuch, Wojciech; Pillath-Eilers, Matthias; Polanska, Joanna; Hermann, Dirk M. (Frontiers in Cellular Neuroscience, 2021)
Astrocytic networks are critically involved in regulating the activity of neuronal networks. However, a comprehensive and ready-to-use data analysis tool for investigating functional interactions between the astrocytes is missing. We developed the novel software package named “Astral” to analyse intercellular communication in astrocytic networks based on live-cell calcium imaging. Our method for analysing calcium imaging data does not require the assignment of regions of interest. The package contains two applications: the core processing pipeline for detecting and quantifying Ca++ events, and the auxiliary visualization tool for controlling data quality. Our method allows for the network-wide quantification of Ca++ events and the analysis of their intercellular propagation. In a set of proof-of-concept experiments, we examined Ca++ events in flat monolayers of primary astrocytes and confirmed that inter-astrocytic interactions depend on the permeability of gap junctions and connexin hemichannels. The Astral tool is particularly useful for studying astrocyte-neuronal interactions on the network level. We demonstrate that compared with purely astrocytic cultures, spontaneous generation of Ca++ events in astrocytes that were co-cultivated with neurons was significantly increased. Interestingly, the increased astrocytic Ca++ activity after long-term co-cultivation with neurons was driven by the enhanced formation of gap junctions and connexin hemichannels but was not affected by silencing neuronal activity. Our data indicate the necessity for systematic investigation of astrocyte-neuronal interactions at the network level. For this purpose, the Astral software offers a powerful tool for processing and quantifying calcium imaging data.